2021
DOI: 10.1016/j.ijppaw.2021.10.009
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Leucocytozoon spp. in nestlings of three wild raptor species including implications on haematological and blood chemistry values

Abstract: Leucocytozoonosis is a vector-borne infection of birds, caused by members of the haemosporidian genus Leucocytozoon . The clinical presentation may range from asymptomatic to severe disease. Consequences of Leucocytozoon infection on blood profiles remain to be described, especially for different host species in the wild. In the current study, the prevalence of Leucocytozoon infection was determined in wild nestlings of three European raptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Severe malaria is caused by Plasmodium blood parasites, while related Leucocytozoon parasites can induce similar conditions in a wide range of avian hosts [ 5 ]. Despite a high prevalence (55%) of Leucocytozoon infection in buzzard nestlings previously found on this study site, research suggests low pathogenicity and minimal impacts on host condition [ 117 ]. Nevertheless, signatures of infection were found in haematological and blood chemistry profiles [ 117 ].…”
Section: Discussionmentioning
confidence: 98%
“…Severe malaria is caused by Plasmodium blood parasites, while related Leucocytozoon parasites can induce similar conditions in a wide range of avian hosts [ 5 ]. Despite a high prevalence (55%) of Leucocytozoon infection in buzzard nestlings previously found on this study site, research suggests low pathogenicity and minimal impacts on host condition [ 117 ]. Nevertheless, signatures of infection were found in haematological and blood chemistry profiles [ 117 ].…”
Section: Discussionmentioning
confidence: 98%
“…However, the function of eosinophiles in birds is still little known. Some previous studies had linked Leucocytozoon infections to higher eosinophil counts in raptors [ 55 , 56 ]. Our data did not reveal significant differences on the leukocyte formula between parasitized and non-parasitized birds.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in accordance with Clark et al (2016) and Wiegmann et al (2021), who found increased H/L rates in Zosterops spp. infected by Microfilariae and raptors infected by hematozoa, respectively [ 56 , 57 ]. In this context, it is important to highlight that the proportion of heterophils and lymphocytes (H/L) is a reliable indicator of immune response to stress or illness in birds, including parasitemia [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with human medicine, elevated levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) are among the possible adverse side effects of Malarone ® treatment [33], but these are known as reversible and not associated with clinical signs [45]. However, when evaluating changes in blood chemistry, it should also be considered that existing haemosporidian infections may account for additional variation [22,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…All individuals examined for blood chemistry values were part of a previous study that analysed changes in blood chemistry in response to Leucocytozoon infection [22]. Here, we expanded the dataset by comparing blood chemistry values of Malarone ® -treated individuals before and after resampling.…”
Section: Blood Chemistrymentioning
confidence: 99%